La réception des écrits de Max Weber sur le confucianisme au Japon et en Asie du Sud-Est - Thomas Brisson (Revue d'anthropologie des connaissances)
The paper tackles the reception of Max Weber’s Sociology of Religion in Japan and in South-East Asia between the 1930s and the 1980s. It starts with Weber’s analysis of the negative relation between Confucianism and Capitalism in the 1920s, with the former being considered an impediment to the rise of modern economy. It then scrutinizes how this thesis progressively diffused in Asia and came to be significantly altered. The paper assumes that Weber’s reception has followed two parallel but partly contradictory paths. On the one hand, his idea of a conservative Confucianism has been dismissed and gradually replaced by the opposite assumption that Confucianism has been instrumental in building an Asian modern capitalism. On the other, nevertheless, his connection between religion and capitalism is still framing the academic debates. In Asia, whereas the content of Weber’s thesis has lost momentum, its formal assumptions have remained highly influential.